Impact of Extractant Type and pH on Yttrium Recycling from End of Life Fluorescent Lamp - Tulay Koc Delice; Gulsah Turker; Huseyin Eren Obuz; Belma Soydas Sozer (Materials Proceedings, 2023)
Rare-earth elements (REEs), which are indispensable for high technology and renewable energy, are becoming more significant due to their distinct properties (e.g., catalytic, metallurgical, magnetic, etc.) and their diverse applications in a wide range of contemporary technologies, environmental initiatives, and economic domains. In the pursuit of an environmentally friendly, sustainable, circular approach, recycling and utilizing secondary rare-earth resources as potential reservoirs of REEs may present an alternative to primary mining, addressing future raw material demands. Secondary REE sources include various products such as fluorescent lamps, light-emitting diodes (LEDs), magnets, wind turbines, electric motors, and batteries. Powders used in fluorescent lamps contain approximately 3% phosphorus, and these powders comprise a high ratio of precious REEs such as Y, Eu, La, Ce, and Tb. This study involves the recovery of yttrium from end-of-life fluorescent lamps. The composition of the end-of-life fluorescent lamp was analyzed using X-ray fluorescence (XRF) and X-ray diffraction (XRD) techniques subsequent to grinding. The leaching process was conducted to investigate the effects of leach parameters on the efficiency of the reaction. In the subsequent phase of the study, a solution obtained with the optimum leaching efficiency was subjected to the purification of Y using the solvent extraction (SX) method. The effect of each different extractant and pH values on Y-recovery were investigated for SX process. Yttrium oxide powders were characterized by XRF and ICP(OES) techniques, and high-purity Y2O3 powders were obtained with high yield.